Revision of the genus Narvesus Stål, 1859 (Hemiptera: Heteroptera: Reduviidae: Stenopodainae) and a new record for Argentina - Fernando, Diez; Coscarón, María Del Carmen (Zootaxa, 2014)
This is a revision of Narvesus Stål, a Neotropical genus with two species: Narvesus carolinensis Stål 1859 and Narvesus minor Barber 1930. Both known species are redescribed and illustrated, including data on male genitalia and new distributional records. We compared with the genus Diaditus Stål.